Weather Information for Garden City, 2021 - E. Russell (Kansas Agricultural Experiment Station Research Reports, 2022)
Summary of 2021 weather for research conducted at the Garden City Kansas Agricultural Experiment Station field location.
Keywords: Garden City weather; 2021 weather; western Kansas weather report